1988
DOI: 10.1037/0096-1523.14.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Haptically perceiving the distances reachable with hand-held objects.

Abstract: Nine experiments are reported on the ability of people to perceive the distances reachable with hand-held rods that they could wield by movements about the wrist but not see. An observed linear relation between perceived and actual reaching distances with the rods held at one end was found to be unaffected by the density of the rods, the direction relative to the body in which they were wielded, and the frequency at which they were wielded. Manipulating (a) the position of an attached weight on an otherwise un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
342
4
4

Year Published

1990
1990
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(376 citation statements)
references
References 22 publications
25
342
4
4
Order By: Relevance
“…The results of Solomon and Turvey's (1988) study and Solomon et al's (1989aSolomon et al's ( , 1989b) studies suggested a simple power function with an exponent less than 1 governing length perception by dynamic touch -specifically, the perceived lengths of cylindrical objects tend to increase as the cube root of 7 t : perceived length « Ii m . With respect to the present experiment, the simple regression of the logarithm of mean H P on the logarithm of I\ was highly significant, r 2 (8) = .95, p < .0001, with a slope of .33 and fiducial limits of .26-.40 (the 95% confidence intervals defining the boundaries within which a parameter is considered to be localized).…”
Section: Resultsmentioning
confidence: 66%
“…The results of Solomon and Turvey's (1988) study and Solomon et al's (1989aSolomon et al's ( , 1989b) studies suggested a simple power function with an exponent less than 1 governing length perception by dynamic touch -specifically, the perceived lengths of cylindrical objects tend to increase as the cube root of 7 t : perceived length « Ii m . With respect to the present experiment, the simple regression of the logarithm of mean H P on the logarithm of I\ was highly significant, r 2 (8) = .95, p < .0001, with a slope of .33 and fiducial limits of .26-.40 (the 95% confidence intervals defining the boundaries within which a parameter is considered to be localized).…”
Section: Resultsmentioning
confidence: 66%
“…The rationale was twofold. First, earlier studies have provided ample evidence that people have definite impressions of both the length (e.g., Pagano et al, 1993;Solomon & Turvey, 1988;Turvey & Carello, 1995) and the center of percussion Cooper et al, 1999) of unseen, wielded rods. A rod's center of percussion, also known as its sweet spot, 1 is the place on the rod at which it is best to hit an object; it produces the least initial shock to the hand.…”
Section: Perceptual Independence: a Prerequisitementioning
confidence: 99%
“…This paradigm is convenient for several reasons. First, using the dynamic touch system, one is capable of perceiving several properties of the hand-held object: length (e.g., Solomon & Turvey, 1988), heaviness (e.g., Amazeen & Turvey, 1996), center of percussion (e.g., Carello, Thuot, Anderson, & Turvey, 1999;Carello, Thuot, & Turvey, 2000), shape (Burton, Turvey, & Solomon, 1990), and width and height (e.g., Turvey, Burton, Amazeen, Butwill, & Carello, 1998). Second, dynamic touch needs to be calibrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, high correlations have been reported between I 1 (either alone or in combination with I 3 ) and the perceived length of an object (Carello, Fitzpatrick, Flascher, & Turvey, 1998;Fitzpatrick et al, 1994;Pagano et al, 1993;Solomon & Turvey, 1988;Solomon, Turvey, & Burton, 1989;Turvey, Burton, Amazeen, Butwill, & Carello, 1998). In addition, perceived object width has been found to correlate with the eigenvalues of the inertia tensor .…”
mentioning
confidence: 99%